Integrating nutrition into environmental impact assessments reveals limited sustainable food options within planetary boundaries - Kyttä, Venla; Ghani, Hafiz Usman; Pellinen, Tiina; Kårlund, Anna; Kolehmainen, Marjukka; Pajari, Anne-Maria; Tuomisto, Hanna L.; Saarinen, Merja (Elsevier BV, 2025)
Environmentally sustainable and nutritionally adequate food consumption and production can include a wide selection of foods, which requires detailed information on individual food products to enable sustainable food choices. The aim of this study was to integrate nutritional aspects in the assessment of environmental sustainability of food products against the planetary boundaries. Methodologically, the model was built on the approaches of nutritional Life Cycle Assessment (LCA) and a planetary boundary-based LCA (PB-LCA) that compares environmental impacts against the assigned share of planetary boundaries. Thus, the model can identify food products that provide sufficient nutrition in relation to their environmental impacts, in accordance with the criteria of the planetary health diet. As a result, we developed Nutrient Index-based Sustainable Food Profiling Model (NI-SFPM) and tested its applicability in an assessment of 559 food products across various food categories, considering the impact categories corresponding to the planetary boundaries of climate change, nitrogen cycling, phosphorus cycling, freshwater use, land-system change, and biodiversity loss. The results demonstrated the model's effectiveness in discerning between food products and food categories based on their environmental performance and nutrient composition. The resulted sustainability ranking of different food categories was in accordance with the current understanding of healthy and sustainable diets. By evaluating the sustainability of food products, the NI-SFPM enables informed decision-making for consumers, policymakers, and food industry stakeholders, assisting in optimizing production processes, sourcing sustainable ingredients, and enhancing product formulations. Through these insights, the NI-SFPM has the potential to drive positive changes in food industry by promoting the development and consumption of environmentally and nutritionally sustainable food products.